Effect on cardiovascular risk of high density lipoprotein targeted drug treatments niacin, fibrates, and CETP inhibitors: meta-analysis of randomised controlled trials including 117 411 patients - Keene,D; Price,C; Shun-Shin,MJ; Francis,DP (BMJ: British Medical Journal, 2014)
Objective To investigate the effects on cardiovascular outcomes of drug interventions that increase high density lipoprotein levels.Design Meta-analysis.Studies reviewed Therapeutic benefit of niacin, fibrates, and cholesteryl ester transfer protein (CETP) inhibitors on cardiovascular events (all cause mortality, coronary heart disease mortality, non-fatal myocardial infarction, and stroke).Results 117 411 patients were randomised in a total of 39 trials. All interventions increased the levels of high density lipoprotein cholesterol. No significant effect was seen on all cause mortality for niacin (odds ratio 1.03, 95% confidence interval 0.92 to 1.15, P=0.59), fibrates (0.98, 0.89 to 1.08, P=0.66), or CETP inhibitors (1.16, 0.93 to 1.44, P=0.19); on coronary heart disease mortality for niacin (0.93, 0.76 to 1.12, P=0.44), fibrates (0.92, 0.81 to 1.04, P=0.19), or CETP inhibitors (1.00, 0.80 to 1.24, P=0.99); or on stroke outcomes for niacin (0.96, 0.75 to 1.22, P=0.72), fibrates (1.01, 0.90 to 1.13, P=0.84), or CETP inhibitors (1.14, 0.90 to 1.45, P=0.29). In studies with patients not receiving statins (before the statin era), niacin was associated with a significant reduction in non-fatal myocardial infarction (0.69, 0.56 to 0.85, P=0.0004). However, in studies where statins were already being taken, niacin showed no significant effect (0.96, 0.85 to 1.09, P=0.52). A significant difference was seen between these subgroups (P=0.007). A similar trend relating to non-fatal myocardial infarction was seen with fibrates: without statin treatment (0.78, 0.71 to 0.86, P<0.001) and with all or some patients taking statins (0.83, 0.69 to 1.01, P=0.07); P=0.58 for difference.Conclusions Neither niacin, fibrates, nor CETP inhibitors, three highly effective agents for increasing high density lipoprotein levels, reduced all cause mortality, coronary heart disease mortality, myocardial infarction, or stroke in patients treated with statins. Although observational studi